(x平方+4x+3)(x平方+6x+8)=24
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 22:37:33
(x平方+4x+3)(x平方+6x+8)=24(x平方+4x+3)(x平方+6x+8)=24(x平方+4x+3)(x平方+6x+8)=24x=0.[(x+2)^2-1][(x+3)^2-1]=24,两
(x平方+4x+3)(x平方+6x+8)=24
(x平方+4x+3)(x平方+6x+8)=24
(x平方+4x+3)(x平方+6x+8)=24
x=0.[(x+2)^2-1][(x+3)^2-1]=24,两个平方减1相称能得24,只能是(4-1)(9-1)=24,所以x=0
(3x平方-x-2)平方=(2x平方+4x-8)平方-(x的平方-5x+6)平方 解方程
(3x平方-x-2)平方=(2x平方+4x-8)平方-(x的平方-5x+6)平方 解方程
(x平方+4x+8)平方+3x(x平方+4x+8)+2x平方因式分解
2x平方+(x+2)平方+(x+4)平方+(x+6)平方=(3x+2)(2x+6)
X(x平方-6x-9)-x(x平方-8x-15)+2x(3-x)其中x=-六分之一
(4x+20)(x的平方-6x+9)/(3x-x的平方)(x的平方+2x-15)
4x的平方—8x+5-3x的平方=6x-2
x的平方—4x+3小于0 x的平方—6x+8
(x平方+4x+3)(x平方+6x+8)=24
3x平方-5x平方y-{2x平方y+6xy平方-[2xy平方-3x平方y+(3x平方y-4xy平方】}
x平方-6x+8分之2,x平方+x-6分之1,12+x-x平方分之3-x尤其是x平方-6x+8,x平方+x-6,12+x-x平方
x平方-6x+8
(x平方+4x)(x平方+4x+8)+16(x平方+4x)(x平方+4x+8)+16
|X平方-3x-4|
化简:x平方-x-2/x平方-x-6除以x平方+4x-5/x平方+2x-10
x平方-4x
X平方-3x
因式分解(x平方+3x)4次方-8(x平方+3x)平方+16